ANALYSIS OF THREE SERVERS CLOSED SERIES QUEUING NETWORK WITH DELAY TIME USING MAX-PLUS ALGEBRA - Rudhito, Marcellinus Andy; Putra, Dewa Putu Wiadnyana (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
Max-Plus Algebra, which is the union of the set of all real numbers with an infinite singleton, equipped with maximum (max) and plus (+) operations, can be used to model and analyze algebraically the dynamics of a closed queuing network. This study aims to analyze the effect of delays in the start time of service activities on a closed series queuing network with three servers. This study is a study based on literature studies, mathematical model studies and simulations assisted by the Scilab computer program. The results show that the max-plus eigenvalue of a closed series queuing network with 3 servers, which is also the periodicity of network dynamics, is the largest service time of the server in the network. Delays in servers with the largest service time will continue to propagate for subsequent schedules. Delays in servers whose service time is not the maximum can still be tolerated, as long as the delay does not exceed the size of the element in the initial max-plus eigenvector, which corresponds to its largest service time. In this case, the system will be able to return to normal according to the original schedule, after undergoing a maximum of 4 stages of the service process since the beginning of the delay. Meanwhile, delays that exceed this will cause network scheduling to be late and will continue to spread to subsequent services.